2009
DOI: 10.2478/s11532-009-0079-y
|View full text |Cite
|
Sign up to set email alerts
|

Acid-base behaviour of sanguinarine and dihydrosanguinarine

Abstract: Acid-base and optical properties of sanguinarine and dihydrosanguinarine were studied in the presence of HCl, HNO 3 , H 2 SO 4 , H 3 PO 4 , CAPSO and acetic acid (HAc) of different concentrations and their mixtures. The equilibrium constants pK R+ of the transition reaction between an iminium cation Q + of sanguinarine and its uncharged QOH (pseudo-base, 6-hydroxy-dihydroderivative) form were calculated. A numerical interpretation of the A-pH curves by a SQUAD-G computer program was used. Remarkable shifts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Previous studies of sanguinarine and chelerythrine showed that the fluorescence of QBAs comes from two distinct species–neutral alkanolamine and positively charged iminium [ 20 , 21 ]. In aqueous solution typical values of pK ROH for QBAs are between 7.7 (chelirubine) and 9 (chelerythrine) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of sanguinarine and chelerythrine showed that the fluorescence of QBAs comes from two distinct species–neutral alkanolamine and positively charged iminium [ 20 , 21 ]. In aqueous solution typical values of pK ROH for QBAs are between 7.7 (chelirubine) and 9 (chelerythrine) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the fluorescence of sanguinarine and chelerythrine is well described [ 20 23 ], knowledge of the fluorescence properties of other QBAs is limited. Fluorescence spectra in aqueous solution and their change upon binding to DNA has previously been reported [ 24 ] and their potential use as probes in fluorescence microscopy and flow cytometry was proposed [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…), as Amresco ® , Solon, Ohio, USA) and sodium hydroxide (reagent grade purity, Penta, Chrudim, Czech Republic) solutions were used for the pH adjustment in a pH interval pH = 2 -11 with steps ∆pH = 0.2 -0.5. All other experimental conditions were in accordance to previous paper [17].…”
Section: Introductionmentioning
confidence: 96%
“…The absorbance values of both alkaloids were measured three times at each pH and the mean values from these measurements were used to calculate of pK R+ . For more details see our previous paper [17].…”
Section: Introductionmentioning
confidence: 99%
“…And the characteristic absorption peaks of SAN appeared at the wavelengths of 270 and 323 nm, further confirming the successful synthesis of SAN@AHEP@Ta 4 C 3 (Figure 1d). 37 Figure 1e shows the hydrated particle size diagram of Ta 4 C 3 , AHEP@Ta 4 C 3 , and SAN@AHEP@Ta 4 C 3 . It can be observed that the particle size of Ta 4 C 3 quantum dots is about 6−8 nm (consistent with Figure 1a), and the particle size of SAN@AHEP@Ta 4 C 3 is about 140−180 nm (consistent with Figure 1b), which is not much different from AHEP@Ta 4 C 3 , indicating that SAN is evenly loaded in the flower-shaped production.…”
Section: ■ Introductionmentioning
confidence: 99%